2021
DOI: 10.3389/fpls.2021.672552
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin Induces Pathogen Resistance Against Pseudomonas syringae Through the Activation of NPR1 in Arabidopsis

Abstract: Flavonoids are well known for the coloration of plant organs to protect UV and ROS and to attract pollinators as well. Flavonoids also play roles in many aspects of physiological processes including pathogen resistance. However, the molecular mechanism to explain how flavonoids play roles in pathogen resistance was not extensively studied. In this study, we investigated how naringenin, the first intermediate molecule of the flavonoid biosynthesis, functions as an activator of pathogen resistances. The transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
(100 reference statements)
0
23
0
Order By: Relevance
“…However, we did not detect significant accumulation of naringenin in tobacco after infection with P. nicotianae by metabolite analysis. Interestingly, naringenin has been shown to induce pathogen resistance against P. syringae through the activation of NPR1 in Arabidopsis 2021, but did not show any antimicrobial activity against P. syringae even at high concentrations in vitro (An et al, 2021). Our results demonstrate that naringenin confers plant defence against P. nicotianae through induction of plant-pathogen resistance in addition to its antimicrobial activity.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, we did not detect significant accumulation of naringenin in tobacco after infection with P. nicotianae by metabolite analysis. Interestingly, naringenin has been shown to induce pathogen resistance against P. syringae through the activation of NPR1 in Arabidopsis 2021, but did not show any antimicrobial activity against P. syringae even at high concentrations in vitro (An et al, 2021). Our results demonstrate that naringenin confers plant defence against P. nicotianae through induction of plant-pathogen resistance in addition to its antimicrobial activity.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, we showed that naringenin induced the accumulation of ROS, which suggests that naringenin might act as a pro‐oxidant. An et al also showed that naringenin induced an ROS burst in plants as a defence against P. syringae (An et al, 2021). SA has been shown to induce pathogen resistance through ROS accumulation and increased expression of PR genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these candidates were also induced by other stresses, with only two genes being more activated by drought (N8DT2) or nematode infection (IRL) than by UV exposure. N8DT2 is responsible for the prenylation of the flavonoid naringenin and is involved in pathogen resistance mediated by the MAPK- and SA-dependent activation of NPR1 [ 93 ]. Likewise, IRL catalyzes the production of isoflavonoid phytoalexins, which are potent antifungal agents and have recently been associated with maintaining redox homeostasis under stress conditions [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, UV-B, heat stress, etc. can activate MPK3/6 signaling, act on the downstream transcription factor EIN3 to induce the accumulation of chitinase or activate the expression of disease process-related proteins (PR) and CAT-encoding genes ( Rakwal et al, 2004 ; Yoo et al, 2008 ; Bethke et al, 2009 ; An et al, 2010 ; An et al, 2021 ; Kumar et al, 2021 ). 12 C ion beam radiation treatment resulted in differential upregulation of mitogen-activated protein kinase 3 (MPK3), mitogen-activated protein kinase 5 (MKK5), disease process-related protein (PR1), chitinase (ChiB) and CAT, while 7 Li PR1 and ChiB were differentially downregulated in the ion beam treated group.…”
Section: Discussionmentioning
confidence: 99%